Peranan Rumah Yatim Al-Hijrah Bone dalam Pembinaan Anak Yatim - Abd. Malik (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2026)
Orphans are a vulnerable social group that requires special attention in education, religious guidance, and character development. The loss of parental roles causes orphans to need continuous assistance to grow and develop optimally. Rumah Yatim Al-Hijrah Bone is a socio-religious institution that plays an important role in fostering orphaned children through various educational and social programs. This study aims to analyze the role of Rumah Yatim Al-Hijrah Bone in the development of orphaned children. This research employs a qualitative approach using literature review, observation, and interviews. Data were collected through direct observation of mentoring activities and interviews with administrators and caregivers. The results indicate that Rumah Yatim Al-Hijrah Bone actively contributes to orphan development through formal and non-formal education, religious guidance, character building, and social assistance. These programs have a positive impact on the spiritual, academic, and social development of orphaned children. Therefore, Rumah Yatim Al-Hijrah Bone plays a strategic role in supporting the development and welfare of orphans in Bone Regency.